The Interplay between Board Gender Diversity, Earnings Quality, and Return Volatility: Considering the Reputation of Corporate Awards - Isnayni Sabila; Rahmawati Rahmawati; Djuminah Djuminah; Endang Dwi Amperawati; Agus Dwianto (Qubahan Academic Journal)
This study investigates the role of board gender diversity and earnings quality on return volatility by examining corporate reputation, as represented by Indonesia's Most Admired Company Award. This study examined 200 samples of companies in Indonesia’s consumer cyclicals sector from 2018 to 2022. The data were analysed using a panel data estimation technique known as the random-effects model. The findings reveal that earnings quality can reduce return volatility, especially for companies that are ranked or have a good reputation. This study provides valuable insights for companies and policymakers, enhancing their understanding of the importance of earnings quality and corporate reputation for company sustainability. Overall, this study contributes to the literature by examining the relationships among board gender diversity, earnings quality, corporate reputation, and return volatility.